Nilai–Nilai Pendidikan Karakter Dalam Gerak Tari Piring Di Sanggar Pelangi Ranah Minang Di Kota Padang - Diah Ayu Anggraini; Fuji Astuti (SENDRATASIK UNP, 2021)
This research aims to describe the educational values of characters and reveal the meaning of character values contained in plate dance in Sanggar Pelangi Ranah Minang Padang. This type of research is qualitative research using descriptive methods. The main instruments in this study are self-research and assisted with supporting instruments such as stationery and cameras. Data collection techniques are carried out by means of library studies, observations, interviews and documentation. Steps to analyze data are data collection, describing data and making conclusions. The results showed that Tari Piring in Sanggar Pelangi Ranah Minang contains character education values that can be used as learning for the surrounding community as well as dance performers. The learning in this case is as an effort to establish a character that Kediri himself and the wider community apply. Piring Dance in Sanggar Pelangi Ranah Minang teaches that people always have a relationship with God, responsibility and curiosity. The educational values of the characters contained in The Plate Dance in Sanggar Pelangi Ranah Minang can be classified as the educational value of characters related to God, Self, others. The educational values of the characters contained in The Plate Dance in Sanggar Pelangi Ranah Minang played a role in the formation of the personality of a characterful and dignified nation.